11x+11y
11(x+y)
Explanation
Step 1
Let
Carlos earns == 11 per hour
x represents the number of hours he worked in May
the,
the amount he earned in Mayis
![11\cdot x=11x](https://tex.z-dn.net/?f=11%5Ccdot%20x%3D11x)
y represent the number of hours he worked in June.
the amount he earned in June was
![11\cdot y=11y](https://tex.z-dn.net/?f=11%5Ccdot%20y%3D11y)
Step 2
the amount of money he earned is May and June is the sum of the values
![\begin{gathered} \text{total}= \\ 11x+11y \\ \text{if we factorize 11} \\ 11(x+y) \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Ctext%7Btotal%7D%3D%20%5C%5C%2011x%2B11y%20%5C%5C%20%5Ctext%7Bif%20we%20factorize%2011%7D%20%5C%5C%2011%28x%2By%29%20%5Cend%7Bgathered%7D)
I hope this helps you
Answer:
(2, 5)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define Systems</u>
y - 3x = 1
2y - x = 12
<u>Step 2: Rewrite Systems</u>
y - 3x = 1
- Add 3x on both sides: y = 3x + 1
<u>Step 3: Redefine Systems</u>
y = 3x + 1
2y - x = 12
<u>Step 4: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em>: 2(3x + 1) - x = 12
- Distribute 2: 6x + 2 - x = 12
- Combine like terms: 5x + 2 = 12
- Isolate <em>x</em> term: 5x = 10
- Isolate <em>x</em>: x = 2
<u>Step 5: Solve for </u><em><u>y</u></em>
- Define equation: 2y - x = 12
- Substitute in <em>x</em>: 2y - 2 = 12
- Isolate <em>y </em>term: 2y = 10
- Isolate <em>y</em>: y = 5
Answer:
C.
Step-by-step explanation:
m1 is greater than m2 because the angle is larger